Educational level and self-care behaviour in patients with heart failure before and after nurse educational intervention. (1st October 2014) - González, Beatriz; Lupón, Josep; Domingo, Maria del Mar; Cano, Lucía; Cabanes, Roser; de Antonio, Marta; Arenas, Miquel; Crespo, Eva; Rodríguez, Margarita; Bayes-Genis, Antoni
Abstract: Background: Self-care is important for heart failure (HF) management and may be influenced by the patient's educational level. Aim: We assessed the relationship of educational level with baseline self-care behaviour and changes one year after a nursing intervention in HF outpatients attending a HF unit. Patients and method: Three hundred and thirty-five HF patients were studied, with a median age of 67 years (P25–75 57–75) and a median HF duration of six months (P25–75 1–36). HF aetiology was mainly ischaemic heart disease (53.4%). Median ejection fraction was 30% (P25–75 24–37%). The functional class was mainly II (66.3%) and III (25.7%). Educational levels were: very low 17.3%; low 62.1%; medium–high 20.6%. Patients were evaluated at the first visit (baseline) and one year after the educational intervention with the nine-item European Heart Failure Self-care Behaviour Scale. Results: Median patient scores differed in the baseline (19 (P25–75 15–26) vs . 16 (P25–75 13–21) vs . 15 (P25–75 12.5–15.5)) and the one-year evaluation (15 (P25–75 13–17) vs . 13 (P25–75 11–15) vs . 12 (P25–75 10–14)) for the three educational levels, respectively, with statistically significant differences between levels ( p =0.007 to p <0.001) except between low and medium-high education at one year ( p =0.057). In the one-year evaluation, self-care behaviour significantly improved in the three educational groups ( p <0.001), with a similar, albeit not statistically significant, magnitude of improvement in all groups. Conclusions: Self-care behaviour at baseline and one year after a nursing intervention was better in patients with a higher education, although the improvement with the intervention was similar irrespective of the educational level.